2011
DOI: 10.1002/ceat.201100033
|View full text |Cite
|
Sign up to set email alerts
|

Flow Field Analysis of Stirred Liquid‐Liquid Systems in Slim Reactors

Abstract: Previous studies have shown the great potential, but also the great challenges, in handling slim reactors often used for polymerization reactions. Experiments and simulations were carried out in reactors with aspect-to-diameter ratios of up to 5, to test and to evaluate the mixing and dispersion efficiency for liquid-liquid systems of single-and multiple-stage impellers. Therefore, power consumption, mixing time and minimum dispersion speed were determined for five different stirrer types under turbulent condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Furthermore, the stirrer speed as well as the concentration of the dispersed phase. All geometric parameters as well as their influence on the fluid dynamics are more extensively described by Maaß et al…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the stirrer speed as well as the concentration of the dispersed phase. All geometric parameters as well as their influence on the fluid dynamics are more extensively described by Maaß et al…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the drop size distribution of an agitated system should not be calculated based on a single average value. Based on extensive CFD simulations, PIV (particle image velocimetry) measurements and comparative PBE model variations (see also Maaß et al), an appropriate description of the spatial inhomogeneity was found using a zonal model. One zone with high energy dissipation rates describes the impeller region and one zone with low energy dissipation rates describes the bulk region of the vessel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been reported the multiple impellers have great potential applications for the single‐and two‐phase systems due to their advantages over the single impeller. A flow analysis in slim reactors revealed multiple impellers should be used rather than the single impeller to save power and allow complete dispersion especially for reactors with the ratios of liquid level to reactor diameter >3.…”
Section: Introductionmentioning
confidence: 99%